Assessment of Decision-making Competence in Preadolescence - Weller, Joshua A.; Levin, Irwin P.; Rose, Jason P.; Bossard, Elaine (Journal of behavioral decision making, 2012)
ABSTRACT Recent research using late adolescent (18–19 years) and adult samples suggests that within‐subject performance on a variety of standard, controlled laboratory tasks reflects a higher‐order positive manifold of decision‐making competence. The present paper extends this important work by testing whether preadolescent children (10‐ to 11‐year‐olds, n = 101) exhibit a similar structural pattern characterizing their decision‐making performance. Performance on “child‐friendly” versions of framing problems, decision matrices, consistency in risk perceptions, and calibration of confidence conformed to a one‐factor solution, comparable with that previously found with older populations. Further, individual differences in effortful control, a temperament dimension related to self‐regulative executive function, was significantly associated with decision‐making competence. Importantly, these measures were predictive of both positive (e.g., completing set goals) and negative behaviors (e.g., missing homework assignments). Results are discussed in terms of the existence of early stable patterns of decision making and rationality and the emergence of systematic individual difference factors in decision making. Copyright © 2011 John Wiley & Sons, Ltd.